Strategi Pemasaran Produk Getas di IKM Barokah Desa Kebundadap Timur, Kecamatan Saronggi - Atfalina Unsa Hidayatin; Ika Wahidawati; Yesi Aprilatul Marisa; Dina Wardana; Moh. Kurdi; Sayyida Sayyida (Jurnal Informasi Pengabdian Masyarakat, 2024)
In facing increasingly complex market dynamics, it is important for SMEs to continue to develop effective marketing strategies. SMEs in the East Kebundadap village have brittle product production activities that are still developing. However, there are a few obstacles in marketing and promotion. This service aims to provide understanding and assistance to SMEs of Getas products in effective and efficient marketing, as well as being able to compete effectively with similar products, as well as increasing the effectiveness of Getas product marketing strategies. This is done so that the production and business of the IKM continues to run. And in the end it can help the economy of the community in the village of East Kebundadap. The methods used are preliminary studies, outreach, mentoring and monitoring. The result of this activity is that SMEs are able to understand and implement marketing strategies such as attractive stickers, developing sales networks, promotions using offline media (pamphlets), and promotions via social media.